As transformações do jornalismo em tempo de fake news: a ascensão da prática de fact-checking como ferramenta de reafirmação do compromisso com os fatos - Henrique Silva, Vinícius (2022)
The article aims to analyze the monitoring of the Fact-Checking initiative of the G1, Fato or Fake, during the month of September 2020 and understand the mechanisms used for verification, as well as investigate the importance of the rise of the practice of checking facts within the current Covid-19 pandemic context. Through Lipmann (2020), Seibt (2019), Kenzo (2019), Silva (2019), Baptista (2019), Bakir & McStay (2018), Marshall (2003) and Wardle and Derakhashan (2017), it was possible to consider that Fact-Checking alone cannot resolve the issue of misinformation, requiring other measures such as the inclusion of digital literacy in public and private schools, regulations on roaming companies and, above all, goodwill of the entrepreneurs responsible for the algorithms to change them.